Adaptive Resource Scheduling Algorithm with QoS Guarantee in WiMAX Mesh Mode - Xiao, L.Y.; Wang, R.; Wang, Z.; Wang, H.N. (International Journal of Online and Biomedical Engineering (iJOE), 2013)
WiMAX is a new wireless metropolitan area networks technology based on IEEE 802.16 standard. WiMAX can provide high-speed connection for Internet. IEEE 802.16 standard is an open broadband wireless access technology, which supports high data rate and multimedia communications. Scheduling plays an important role in providing quality of service (QoS) support to multimedia communications. IEEE 802.16e defined two topology architectures: point-to-multipoint and mesh. In this paper, an adaptive resource scheduling algorithm with QoS guarantees is proposed for WiMAX mesh mode. The scheduling order is determined according to the priority, QoS satisfaction and topology information of service flows in this algorithm. The system throughput, rtPS packet loss rate and nrtPS throughput of different algorithms are compared by simulation. Simulation results show that the proposed adaptive resource scheduling algorithm can meet various QoS requirements and increase the system throughput.